Patients' beliefs about medicines and adherence to medication in ischemic heart disease - Dias, António; Pereira, Carlos; Monteiro, Maria João; Santos, Célia (Elsevier, 2014)
Introduction: The phenomenon of adherence to treatment is a motive of worry from the scientific community, since it is considered as a worldwide problem of high magnitude. The implications are of great relevance in morbidity, mortality, in the significant increase in the consumption of health care and in the costs to the health system, particularly in patients with ischemic heart disease. We intend to evaluate adherence to treatment and relate beliefs about medicines with adherence to treatment. Material and methods: This study is descriptive-correlational and cross-sectional. It was performed on 254 patients with ischemic heart disease who were in follow-up consultation in the hospital at the time of the questionnaire application. Data collection was performed through a self-administered questionnaire, integrating the following scales: Measure Adherence to Treatment and Beliefs about Medicines Questionnaire. Results: The patients had a mean age of 66.94 years (SD = 11.62), 74% were male, 73.2% were married, 69.3% had education up to the “4th grade”, 57.1% lived in the village, 70.1% were retired and 49.6% had an income below “one minimum wage”. We found that 50.4% of patients did not adhere to treatment. Women had a strong belief in the specific needs of the prescribed medication, while men expressed greater belief in relation to long-term side effects (P > .05). Patients who expressed a low belief about the harmful potential of medicines revealed predictors of adherence to medication. Conclusion: The results are consistent with previous studies in which individuals with lower beliefs in specific concerns reported higher rates of adherence to medication.
Keywords: Aged; Cross-Sectional Studies; Female; Humans; Male; Medication Adherence; Middle Aged; Myocardial Ischemia; Attitude to Health; Health Knowledge, Attitudes, Practice